Recovering paleoearthquake slip record in a highly dynamic alluvial and tectonic region (Hope Fault, New Zealand) from airborne lidar. Issue 6 (18th June 2015) - Manighetti, I.; Perrin, C.; Dominguez, S.; Garambois, S.; Gaudemer, Y.; Malavieille, J.; Matteo, L.; Delor, E.; Vitard, C.; Beauprêtre, S.
Abstract: Knowing the slip amplitudes that large earthquakes produced in prehistorical times is one key to anticipate the magnitude of large forthcoming events. It is long known that the morphology is preserving remnants of paleoearthquake slips in the form of fault‐offset landforms. However, the measured offsets that can be attributed to the most recent paleoearthquakes are generally few along a fault, so that they rarely allow recovering the slip distributions and largest slips of these earthquakes. We acquired 1 m resolution airborne lidar data on a 30 km stretch of a fast‐slipping strike‐slip fault (eastern Hope Fault, New Zealand) located in a region of high alluvial dynamics where landforms are rapidly evolving. Data analysis reveals >200 offset landforms; only 30% allow a good to moderate quality offset measurement. From these good to moderate quality measures, we recover the slip‐length distributions and largest slips of the four most recent large paleoearthquakes and find evidence of 4–6 prior events. The record suggests that large earthquake slip recurred in multiples of about 4 m along the 30 km stretch. Although they have larger uncertainties, the more numerous lower‐quality offsets that we also measured reveal a similar earthquake slip record. This shows that, although offset landforms are partly degraded in dynamically active landscapes, they store valuable information on paleoearthquake slips. This information might be recovered provided that the morphology is analyzed at high resolution and "continuously" over a significant fault length. Remote lidar data are powerful to perform such analyses. Key Points: New airborne lidar data reveal >200 lateral offsets on eastern Hope Fault Statistical analysis of offsets reveals a rich record of paleoearthquake slips Large paleoearthquakes on eastern Hope Fault recurred by multiples of about 4 m